Odpowiedzi

Najlepsza Odpowiedź!
2009-12-13T23:37:25+01:00
x - y = 3 /*5
-5x + 10y = -10
5x-5y=15
-5x+10y=-10
5y=5/:5
y=1
x-y=3
x-1=3
x=3+1
x=4
y =1

6x + y = 3
3x + jedna druga y = 5/*(=2)
6x + y = 3
-6x-1y=-10
y=-7
6x-7=3
6x=3+7
6x=10/:6
x=1,6

2 1 2
2009-12-13T23:38:13+01:00
A)
x - y = 3
-5x + 10y = -10

x=3+y
-5(3+y) + 10y=-10

x=3+y
-15-5y+10y=-10

x=3+y
5y=-10+15

x=3+y
5y=5 /:5

x=3+y
y=1

x=4
y=1


b)
6x + y = 3
3x + ½ y = 5

y=3-6x
3x + ½(3-6x)=5

y=3-6x
3x+³/₂-3x=5

y=3-6x
x=0

y=3-6*0
x=0

y=3
x=0

POZDRAWIAM :)